Evaluation of the intensity of gingival melanin pigmentation at different age groups in the Indian population: An observational study - Palak Janiani; Pragathi R Bhat; Vijay A Trasad; Anirudh B Acharya; Srinath L Thakur (Wolters Kluwer Medknow Publications, 2018)
Background: The brownish-black pigmentation of the gingiva has been reported in several countries. However, the available literature pertaining to the Asian population suggests that this pigmentation is more predominant in individuals with dark complexion. Although there is available literature on the intensity of gingival pigmentation with different age groups in Japanese and Israel population, no such literature pertaining to age and intensity of melanin pigmentation is available in the Indian population. Aim: This study aims to observe the intensity of melanin pigmentation in different age groups in the Indian population. Methods and Materials: Intensity of melanin pigmentation was observed by the gingival melanin pigmentation index as given by Ponnaiyan et al. in 250 individuals who were grouped under the age group of 0-5 years, 6-9 years, 10-12 years, 13-15 years, and 16-20 years. Each group comprised 25 individuals. Results and Conclusion: The results were subjected to statistical analysis so as to observe the intensity of melanin pigmentation at different age groups in the Indian population. It was concluded that with age, the intensity of gingival melanin pigmentation, as well as its distribution to the posterior gingiva was increased. As age increased, gingival pigmentation was more in the attached and interdental papilla, while in the younger age groups, it was confined either only to the interdental, marginal or attached gingival, or both depending on the skin color.